Efeitos do consumo de nitrato inorgânico (NaNO3) sobre a longevidade e envelhecimento de ratos Wistar - Carvalho, Lucas Rannier Ribeiro Antonino (2021)
The search for interventions and drugs that increase longevity and decrease the effects of time on the organism (aging), is as old as humanity itself. Based on recent descriptions of the beneficial effects of nitrates on various health conditions, the consumption of vegetables rich in this salt, such as spinach and beet leaves, has been encouraged. However, the chronic effects of this supplementation have not yet been described and, due to its toxic potential, longterm evaluations are urgent and necessary. Therefore, the objective of this work was to evaluate the effects of sodium nitrate consumption on the longevity and aging of elderly rats. For that, Wistar rats of both sexes, 15 months old, were used, continuously supplemented with drinking water (placebo) or sodium nitrate solution (NaNO3 - 10mM), until natural death by senescence. During the treatment period, the animals were submitted to weekly clinical follow-ups and laboratory tests every three months. After death, vascular reactivity was evaluated and samples were collected for histopathological analysis and determination of the cause of death. The results show that supplementation with inorganic nitrate, for long periods, does not alter the life span and aging of individuals. In addition, chronic consumption was responsible for a significant improvement in the effect and sensitivity of vasoconstrictor and vasodilator substances, suggesting a significant improvement in vascular function, with no evidence of tolerance. In the laboratory follow-up, no changes caused by nitrate, regardless of gender, were shown, only changes related to healthy aging. Similar to the diagnosis of the cause of death, in which alterations caused by aging have been described in almost all organic systems, however, there were no significant differences between groups. Thus, it was possible to conclude that long-term supplementation with inorganic nitrate does not significantly interfere with the life span and healthy aging process. Suggesting that it is a safe and easily accessible intervention for long-term consumption. However, its effects appear to be dosedependent and studies that assess its cost-benefit are needed.